Non-ordinary state-based peridynamic fatigue modelling of composite laminates with arbitrary fibre orientation. (August 2022) - Cao, Xingfeng; Qin, Xuda; Li, Hao; Shang, Shuai; Li, Shipeng; Liu, Haitao
Highlights: To precisely describe the failure process of CFRP laminates, matrix and fibre bonds were introduced within the plies, normal and shear bonds were introduced to transfer the interaction force between the plies in the nonordinary state-based peridynamics composite model. A nonordinary state-based peridynamics fatigue simulation model of composite materials was established by combining the fatigue theory of peridynamics and Paris-Erdogan law, and the corresponding model parameters acquisition method was proposed. The failure process (crack initiation and propagation) in different laminae of multidirectional CFRP laminate under the action of tensile or fatigue loading can be obtained based on the proposed model. Abstract: For the safe application of carbon fibre-reinforced polymer (CFRP) materials in engineering structures, fatigue life prediction and failure modelling are essential. In this paper, an application of a nonordinary state-based peridynamics (NOSB-PD) approach for the fatigue failure prediction of multilayer CFRP was presented. To characterize the structure of composite laminates, matrix and fibre bonds were introduced within the plies, and normal and shear bonds were introduced between the plies. The fatigue simulation model of composite materials was established by combining the fatigue theory of peridynamics and Paris-Erdogan law, and a method to obtain model parameters was proposed. To demonstrate the accuracy of the model, tension and fatigue experiments were conducted. By comparing the results of tensile and fatigue experiments, it was shown that the model developed in this paper can accurately predict the failure process of multidirectional CFRP laminate under the action of tensile or fatigue loading. The crack initiation and propagation for different laminae during the tensile and fatigue processes can be obtained from the proposed model.